Big Fishes in Small Ponds: Ability Rank and Human Capital Investment - Benjamin Elsner; Ingo Isphording (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We study the impact of a student's ordinal rank in a high-school cohort on educational attainment several years later. To identify a causal effect, we compare multiple cohorts within the same school, exploiting exogenous variation in cohort composition. We nd that a student's ordinal rank in high-school signi cantly affects educational outcomes later in life. If two students with the same ability have a different rank in their respective cohort, the student with the higher rank is signi cantly more likely to nish high-school, to attend college, and to complete a 4-year college degree. These results suggest that students under- invest in their human capital if they have a low rank within their cohort even though they have a high ability compared to most students of the same age. Exploring potential channels, we nd that students with a higher rank have higher expectations about their future career, and feel that they are being treated more fairly by their teachers.
Keywords: I23; I21; J24; 330